Distance from practice moderates the relationship between patient management involving nurse telephone triage consulting and patient satisfaction with care. (July 2015) - Calitri, Raff; Warren, Fiona C.; Wheeler, Benedict; Chaplin, Katherine; Fletcher, Emily; Murdoch, Jamie; Richards, Suzanne; Taylor, Rod S.; Varley, Anna; Campbell, John
Abstract: The ESTEEM trial was a randomised-controlled trial of telephone triage consultations in general practice. We conducted exploratory analyses on data from 9154 patients from 42 UK general practices who returned a questionnaire containing self-reported ratings of satisfaction with care following a request for a same-day consultation. Mode of care was identified through case notes review. There were seven main types: a GP face-to-face consultation, GP or nurse telephone triage consultation with no subsequent same day care, or a GP or nurse telephone triage consultation with a subsequent face-to-face consultation with a GP or a nurse. We investigated the contribution of mode of care to patient satisfaction and distance between the patient׳s home and the practice as a potential moderating factor. There was no overall association between patient satisfaction and distance from practice. However, patients managed by a nurse telephone consultation showed lowest levels of satisfaction, and satisfaction for this group of patients increased the further they lived from the practice. There was no association between any of the other modes of management and distance from practice.